The optimization of microcapsule encapsulating kaffir lime leave extract using complex coacervation - Ruangsawang, Saranya - (Science Essence Journal, 2020)
The optimization of microcapsule encapsulating of the extract from kaffir lime leaves was developed by complex coacervation technique and freeze-drying technique. A central composite design (CCD) was employed microcapsule encapsulation (condition as level of gelation at 10% and 30% and arabic gum at 20% and 40%). The optimum condition was encapsulated with gelatin 20% and arabic gum 20% (1:1) and was used as wall materials. These were mixed with 10% of extract in extra virgin olive oil as core materials and the ratio of wall materials and core material was 2:1. L*, a*, b*, moisture content, water activity, encapsulation efficiency and citronellal were 65.29, -1.90, 51.09, 1.51, 0.250, 80.25 and 20.38 mg/g of microcapsule, respectively. The particle morphology by scanning electron microscopy (SEM) showed that microcapsules were irregular shape and various size.